POVERTY, INCOME DISTRIBUTION AND DETERMINANTS OF POVERTY AMONG TEACHERS IN PRE-TERTIARY SCHOOLS IN GHANA - Havi, Emmanuel Dodzi K. (European Scientific Journal, ESJ, 2015)
This study looks at poverty and its determinants among pre-tertiary schools teachers in the Eastern Region of Ghana. The study adopted the national moderate poverty line in GLSS4 which was updated using the consumer price index. The objectives of the study were to find out the poverty status of teachers and its determining factors using poverty indices and binary logistic regression model. It was found out that on average teachers are not poor relative to the poverty line. The result showed that large-households were poorer in relation to the small-households; maleteachers were also poorer as compared to female ones. Also, those who spend more years in Ghana Education Service were poorer; poverty diminishes with advancement in educational level. Also, income was fairly distributed. Finally, the small-household size and spouse with tertiary and secondary educational level were significant determinants of the teacher’s poverty. The study recommends that teachers should improve upon their educational level and keep smaller household to improve their wellbeing.